2001
DOI: 10.1021/ol0164684
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Directed Formation of Three-Dimensional M3L2 Trigonal-Bipyramidal Cages

Abstract: [reaction: see text] The simple combination of two angular tritopic pyridine donor linkers (109 degrees bond angle) with three ditopic platinum acceptors (90 degrees bond angle) leads to essentially quantitative formation of self-assembled M(3)L(2) trigonal-bipyramidal (TBP) supramolecular species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 20 publications
(12 reference statements)
1
29
0
Order By: Relevance
“…Tris(4-pyridyl)methanol (25) has all of the attributes necessary to function as the tritopic vertex, as shown by way of its single-crystal X-ray structure (Figure 3a 23 Dodecahedra 28 and 29 are characterized by multinuclear NMR, again showing the overall assemblies as entities of high symmetry, and ESI-MS data, which give both parent peaks, with the corresponding loss of triflate anions, and fragmentation patterns consistent with the proposed macromolecular aggregates. 23 While the definitive proof provided by an X-ray structure could not be obtained to date, most likely due to the size and high symmetry of such entities, two additional methods of product elucidation provide strong evidence for the structural assignment.…”
Section: Scheme 2 Self-assembly Of Truncated Tetrahedramentioning
confidence: 67%
See 1 more Smart Citation
“…Tris(4-pyridyl)methanol (25) has all of the attributes necessary to function as the tritopic vertex, as shown by way of its single-crystal X-ray structure (Figure 3a 23 Dodecahedra 28 and 29 are characterized by multinuclear NMR, again showing the overall assemblies as entities of high symmetry, and ESI-MS data, which give both parent peaks, with the corresponding loss of triflate anions, and fragmentation patterns consistent with the proposed macromolecular aggregates. 23 While the definitive proof provided by an X-ray structure could not be obtained to date, most likely due to the size and high symmetry of such entities, two additional methods of product elucidation provide strong evidence for the structural assignment.…”
Section: Scheme 2 Self-assembly Of Truncated Tetrahedramentioning
confidence: 67%
“…30 As in the successful formation of cuboctahedron 24 and adamantanoid 41, the leniency of the design methodology can be put to the test. In so doing, tritopic, nonplanar, ∼109°linkers, tris(4-pyridyl)methanol (25), adamantyl/ ethynyl-containing tris(pyridyl) subunit 30, and extended building block 45 (Chart 5), yield related, somewhat distorted trigonal prisms 46, 47, and 48, respectively, with clip 42 (Scheme 9). 31 After precipitation and anion-exchange with KPF 6 , the multinuclear NMR spectra for polyhedra 43, 44, 46-48 all exhibit signals consistent with highly symmetrical entities, while the elemental analysis data for each correspond well to the theoretical values.…”
Section: Other Coordination Cagesmentioning
confidence: 99%
“…398,399 A [2 + 3] self-assembly reaction between ~ 109° tripodal angular unit 324 and generic 90° angular units such as cis -Pt(PMe 3 ) 2 (OTf) 2 ( 38 ), cis -Pt(dppp)(OTf) 2 ( 52 ) and cis -Pt(dppe)(OTf) 2 ( 325 ) resulted in trigonal bipyramidal cages 326-328 (Scheme 86). 398 Multinuclear NMR studies and mass spectrometric analysis confirmed the formations of these cages. Similarly, the use of flexible tritopic tectons containing amide 399 and ester 400 functionalities resulted in the exclusive formation of trigonal bipyramidal cages.…”
Section: Three Dimensional (3d) Nanoscopic Cagesmentioning
confidence: 99%
“…TWO-AND THREE-DIMENSIONAL FRAMEWORKS 367 by the steric hindrance and rigidity of the tib ligand [42,43]. The different structure and topology of 2 and 3 indicate that the nature of organic ligands has great influence on the assembly and structure of metalorganic frameworks.…”
Section: Complex [Ag(titmb)(pph 3 )](Cf 3 So 3 )·15h 2 O (3)mentioning
confidence: 99%